Spirit Inovasi dan Makna Kewirausahaan di Era Ekonomi Digital: Studi Naratif pada Pengalaman Pelaku Bisnis Startup - Hamsina Hamsina; Romansyah Sahabuddin; Muhammad Rakib; Ichwan Musa (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to understand how the spirit of innovation and the meaning of entrepreneurship are constructed through the lived experiences of startup business actors in the digital economy era. Using a qualitative narrative inquiry approach within the social constructivist paradigm, this research explores how startup entrepreneurs interpret innovation, resilience in the face of failure, and social responsibility as integral parts of their entrepreneurial identity. Data were collected through in-depth interviews, non-participant observation, and document analysis of startups in the technology, education, and creative economy sectors in Indonesia. Narrative thematic analysis reveals that innovation is understood not merely as a business strategy but also as a form of self-expression and the construction of entrepreneurial identity. Failure is perceived as a reflective learning process that shapes resilience and generates new meaning in the entrepreneurial journey. Moreover, entrepreneurship is interpreted as a meaningful journey that integrates economic goals with social and moral values. The digital ecosystem functions as a social space where entrepreneurial values are negotiated, shared, and reinforced through interaction and collaboration. These findings affirm that entrepreneurship in the digital era is a social process involving creativity, ethical reflection, and sustainable innovation. Theoretically, this study contributes to expanding the understanding of entrepreneurship as a social practice, while practically emphasizing the importance of reflective learning and value awareness in building a sustainable and meaningful startup ecosystem for society.